ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SECARA ONLINE MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Ria Lolita; Almasdi Syahza; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to find out the influence of products, promotions, prices and distribution on online purchasing decisions of Students of Economic Education, Riau University. The number of samples used in the study was 80 students who made purchases online more than twice. The types of data used in this study are primary data in the form of products, promotions, distribution prices and online purchasing decisions. The method of data collection uses questionnaires. The analytical techniques used in this study are multiple linear regression analyses. The results showed that there was a significant influence between products, promotions, prices and distribution on online purchasing decisions on students of Economic Education, Riau University.Key words: Prodct, Promotion, Price, Place and Online Purchase Decision